Factors Determining the Marketing Managerial Efficiency (With Reference to the Edible Oil Entrepreneurs in Karnataka) - Manjunatha, K. (Ushus Journal of Business Management, 2021)
In India, in the recent decades there has been the emergence of modernised form of edible oil industry and suitable marketing strategies have been designed with an eye to earn enormous foreign exchange. However the current levels of productivity and quality of edible oils and the by-products are not adequate for meeting national requirement and do not match with international standards. Among several reasons for this state of affairs in the industry, one of the most striking lacuna is, inefficient marketing management of the enterprises. In this study, an effort is made to identify the factors that comprise marketing managerial efficiency and specific recommendations are made to improving the marketing managerial efficiency. Managerial efficiency with special emphasis on marketing can be operationally defined as the "degree to which the entrepreneur is able to adopt the practice the effectiveness factors for the purpose of achieving maximum profitability in the enterprise and high degree of consumer satisfaction."